Recombination Landscape Divergence Between Populations is Marked by Larger Low-Recombining Regions in Domesticated Rye. (11th June 2022) - Schreiber, Mona; Gao, Yixuan; Koch, Natalie; Fuchs, Joerg; Heckmann, Stefan; Himmelbach, Axel; Börner, Andreas; Özkan, Hakan; Maurer, Andreas; Stein, Nils; Mascher, Martin; Dreissig, Steven
Abstract: The genomic landscape of recombination plays an essential role in evolution. Patterns of recombination are highly variable along chromosomes, between sexes, individuals, populations, and species. In many eukaryotes, recombination rates are elevated in sub-telomeric regions and drastically reduced near centromeres, resulting in large low-recombining (LR) regions. The processes of recombination are influenced by genetic factors, such as different alleles of genes involved in meiosis and chromatin structure, as well as external environmental stimuli like temperature and overall stress. In this work, we focused on the genomic landscapes of recombination in a collection of 916 rye ( Secale cereale ) individuals. By analyzing population structure among individuals of different domestication status and geographic origin, we detected high levels of admixture, reflecting the reproductive biology of a self-incompatible, wind-pollinating grass species. We then analyzed patterns of recombination in overlapping subpopulations, which revealed substantial variation in the physical size of LR regions, with a tendency for larger LR regions in domesticated subpopulations. Genome-wide association scans (GWAS) for LR region size revealed a major quantitative-trait-locus (QTL) at which, among 18 annotated genes, an ortholog of histone H4 acetyltransferase ESA1 was located. Rye individuals belonging to domesticated subpopulations showed increased synaptonemal complex length, but no difference in crossover frequency, indicating that only the recombination landscape is different. Furthermore, the genomic region harboring rye ScESA1 showed moderate patterns of selection in domesticated subpopulations, suggesting that larger LR regions were indirectly selected during domestication to achieve more homogeneous populations for agricultural use.